Computer simulation of the effort states of the teeth’s hard tissues - Kierklo, Anna; Tribiłło, Rościsław; Walendziuk, Adam (Computer Assisted Methods in Engineering and Science, 2000)
The study presents a class of effort of brittle media problems. The model of human tooth with non-carious cervical lesion was analysed. Regions of the most disadvantageous loads was determined.